2009
DOI: 10.1098/rspb.2009.0528
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem service benefits of contrasting conservation strategies in a human-dominated region

Abstract: The hope among policy-makers and scientists alike is that conservation strategies designed to protect biodiversity also provide direct benefits to people by protecting other vital ecosystem services. The few studies that have examined the delivery of ecosystem services by existing conservation efforts have concentrated on large, 'wilderness'-style biodiversity reserves. However, such reserves are not realistic options for densely populated regions. Here, we provide the first analyses that compare representatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
2
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 40 publications
(61 reference statements)
2
88
2
5
Order By: Relevance
“…For example, animal welfare is considered in the UK National Ecosystem Assessment [13], yet its beneficiaries are not human unless we consider the satisfaction of concerned humans (in which case any ecological state of affairs that makes someone happier is an ES). Meanwhile, the biodiversity of an area [19] is sometimes considered an ES, and a subtle semantic shift from 'biological diversity' as an index (an intangible metric of diversity) [20] to 'biodiversity' being an actual aggregate (almost a synonym for 'assemblage') [21] allows biodiversity to be simultaneously presented as also underpinning all other ES and having 'existence value' [5]. The value of such concepts of biodiversity is not in question, but to construe any of them as a process, output or human benefit seems illogical.…”
Section: What Exactly Is An Ecosystem Service?mentioning
confidence: 99%
“…For example, animal welfare is considered in the UK National Ecosystem Assessment [13], yet its beneficiaries are not human unless we consider the satisfaction of concerned humans (in which case any ecological state of affairs that makes someone happier is an ES). Meanwhile, the biodiversity of an area [19] is sometimes considered an ES, and a subtle semantic shift from 'biological diversity' as an index (an intangible metric of diversity) [20] to 'biodiversity' being an actual aggregate (almost a synonym for 'assemblage') [21] allows biodiversity to be simultaneously presented as also underpinning all other ES and having 'existence value' [5]. The value of such concepts of biodiversity is not in question, but to construe any of them as a process, output or human benefit seems illogical.…”
Section: What Exactly Is An Ecosystem Service?mentioning
confidence: 99%
“…However the choice of the indicators was constrained by data availability, as in most ES mapping studies (Eigenbrod et al 2009;Bai et al 2011;Luck et al 2012). Biodiversity provision was derived from maps of species richness and endemism at the country scale.…”
Section: Strengths and Limitations Of The Approachmentioning
confidence: 99%
“…Third, some studies compare ES priority areas with ES provision. For example, studies showed that habitats under conservation (for example in protected areas) provide more regulating and cultural ES than other habitats in Europe (Eigenbrod et al 2009;Maes et al 2012b). Most of these studies focus on the effects of biodiversity conservation policies, such as protected areas or agrienvironmental schemes, on other ES (Chan et al 2006;Egoh et al 2009Egoh et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of recent reviews have highlighted the need for landscape-scale analyses of ecosystem services, to understand spatial variability in their production and flow (Anton et al 2010;de Groot et al 2010;Balmford et al 2011), the spatial analysis of ecosystem services is still at a relatively early stage (Martinez-Harmsincreased rigour in methodologies (Crossman, Bryan, et al 2013). Examples of recent studies include analyses of the impacts of land-use change on ecosystem services at national (Eigenbrod et al 2009), regional (GrĂȘt-Regamey et al 2008Li et al 2010;Liu et al 2010;Swetnam et al 2010) and catchment (Martinez et al 2009) scales, as well as investigations designed to support spatial planning and management decisions both in terrestrial (Egoh et al 2008;Petz & van Oudenhoven 2012) and marine environments (White et al 2012). However, few previous studies have explicitly considered the potential impact of landscapescale approaches to biodiversity conservation on the provision of ecosystem services.…”
Section: Introductionmentioning
confidence: 99%